A comparison of teacher’s involvement in curriculum development in developing and developed countries: a case study of Namibia - Matiki, DesRee Sabata; Chibambo, Mackenzie Ishmael; Divala, Joseph Jinja (Frontiers in Education, 2023)
Curriculum development is an on-going process which involves different stakeholders such as teachers, parents, curriculum specialists, academic institutions and the general public. The involvement of all these stakeholders is essential if such curriculum initiatives are to become successful. Accordingly, this study sought to determine how teachers are involved in the curriculum development processes in Namibia. It did this by examining related literature from selected developing and developed countries on teacher involvement and participation during curriculum development processes. It further deployed a qualitative research design which had a sample size of eleven secondary school teachers who were interviewed, and six NIED officials who filled in questionnaires. The empirical data were thematically analyzed in light of the literature review and Pierre Bourdieu’s Capital and Class Distinction as a theoretical framework. This theory was mainly selected for its ability to illuminate issues of power-relations and exclusions, and how powerful individuals manage to advance and sustain their political interests through manipulation of curriculum processes and content as well as the individuals who use that curriculum. Key findings revealed that in many developing countries teachers are systematically excluded from curriculum development processes even though they (the teachers) are the most critical stakeholders owing to the fact that they are the ones who interact with the educational content as well as the students every day. The findings also demonstrated that secondary school teachers in Namibia did not meaningfully participate during the key stages of curriculum development processes. These findings affirmed the assumptions that teacher voices are mostly discounted during curriculum development processes in many countries despite the centrality of their roles and functions. The study further established that Namibia, like many other countries across the globe, use the top-down (pipes) approaches when developing their curricula unlike developed countries such as Australia, Finland, Singapore and others.